(3GdYdGeI GdeTghQI hMeGjJgG Vef GJaGbjI GdLhGfH GdeJUdI HGdJLGQI ef Mbhb GdedcjI GdacQjI (B((3JQHS(B) (TRIPS) (3hbGfhf GdYdGbGJ GdJLGQjI GdGQOfi (B/ s - (3YHOGddg MejO SdjeGf GdZhjQjs; (3SejMI GdbdjhHj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3eeG dG Tc ajg Gf GdYdGeGJ GdJLGQjI dgG GgejI HGdZI aQVJ faSgG ai eLGd GdJLGQI hGdefGaSI hLhOI GdefJLGJ (B: (3hbO GUOQJ ZGdHjI Ohd GdYGde bhGfjf JfXe JSLjd dYdGeGJ GdJLGQjI hMeGjJgG (B: (3ceG hVYJ GdGJaGbjGJ GdOhdjI bhGYO heHGOF dMeGjI GdYdGeGJ GdJLGQjI hHGbi YfGUQ GdedcjI GdacQjI Ydi GdeSJhi GdhWfi hGdOhdj GdbVGA GdGQOfi WhQ eaghe MeGjI GdYdGeGJ GdeTghQI hGSJfO ai MeGjJgG Ydi MeGjI GdeSJgdc ef GdhbhY ai GdZT hGdJVdjd (B: (3hGSJbQ GdbVGA GdGQOfi Ydi MeGjJgG HZV GdfXQ Yf JSLjdgG Gh GSJYeGdgG ai GdeedcI (B: (3h GKQ UOhQ bGfhf GdYdGeGJ GdJLGQjI cad GdeTQY MeGjI GdYdGeI GdeTghQI GSJKfGAG ef eHOGi GbdjejI hJNUjU JSLjd GdYdGeI GdbGfhf GdGQOfi jTJQW JSLjd GdYdGeI dMeGjJgG eOfjG hLRGFjG hchf ZGdHjI GdYdGeGJ GdeTghQI ZjQ eSLdI ai GdeedcI (B: (3JONd GdeTQY hGhQO fUG ai bGfhf GdefGaSI ZjQ GdeTQhYI haQ HehLHI MeGjI GdYdGeGJ GdJLGQjI GdeSJYedI ai GdeedcI ShGA GcGfJ eSLdI Ge ZjQ eSLdI hGdJi JUH ai eUdMI GdYdGeGJ GdeTghQI HWHjYI GdMGd gPG hjedc eGdc GdYdGeI GdeTghQI OGNd GdGQOf GdJbOe HWdHGJ efY hGHWGd hTWH JSLjd GjI YdGeI SLdJ ai GdeedcI hJTcd GYJOGA Ydi YdGeJg hjedc GdMb ai GbGeI OYhi ddeWGdHI HGdJYhjV habG dGMcGe bGfhf GdefGaSI ZjQ GdeTQhYI (B: (3GdG Gfg dG jedc GdMb ai GbGeI OYhi LRGFjI hGdJi ef TQhW GbGeJgG Gf Jchf GdYdGeI eSLdI ai GdeedcIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2006s
(3HHdjhLQGajG(B: (3UaMGJ (B411-424s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdYdGbI GdJLGQjIs; (3JOHSs; (3GdbGfhf GdCQOfjs; (3efXeI GdJLGQI GdYGdejIs; (3GdTGQGJ GdeejRIs; (3GdYdGeI GdeTghQIs; (3eHOC JNUjU JSLjd GdYdGeIs; (3GdefGaSI ZjQ GdeTQhYIs; (3GdMeGjI GdLfGFjI ddYdGeI GdeTghQIs; (3GdefXeGJ GdOhdjI aj eLGd MeGjI GdYdGeGJ GdJLGQjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs